Development and Characterization of Montmorillonite‐Based Hybrid Materials for pH‐Responsive Drug Delivery. Issue 7 (11th February 2021) - Obireddy, Sreekanth Reddy; Subbarao, Subha Marata Chinna; Venkata, Krishna Rao Kummari Subba; Lai, Wing‐Fu
Abstract: This study reports the development of montmorillonite (MMT)‐based hybrid systems for pH‐responsive drug delivery. During fabrication, MMT is first modified with dimethyl sulfoxide (DMSO) and methanol (MeOH), with the generated hybrid materials being designated as MMTDMSO and MMTMeOH, respectively. The hybrid materials are then intercalated with DOX for drug delivery purposes. Results of XRD and DSC reveal that DOX is successfully intercalated into the MMT interlayers. In vitro drug release studies of the DOX‐loaded hybrid materials are investigated at pH 4.5 and 7.4 at 37 °C. The cytotoxicity of the materials is studied in vitro by using human breast cancer cells (MCF‐7) as a model. Results suggest that our hybrid materials are carriers enabling effective, sustained and controlled drug release. Abstract : Montmorillonite (MMT)‐based hybrid systems are designed, synthesized, and characterized as pH‐responsive drug carriers. During fabrication, MMT is modified with either dimethyl sulfoxide (DMSO) or methanol (MeOH), followed by drug loading mediated by the intercalation process. Our hybrid materials display high drug loading efficiency and pH‐responsive drug release.